Recombinant protein expression in Escherichia coli: advances and challenges - Rosano, Germán L.; Ceccarelli, Eduardo A. (Frontiers in Microbiology, 2014)
Escherichia coli is the organism of choice for the production of recombinant proteins. Its use as a cell factory is well-established and it has become the most popular expression platform. For this reason, there are many molecular tools and protocols at hand for the high-level production of recombinant proteins, such as a vast catalog of expression plasmids, a great number of engineered strains and many cultivation strategies. We review the different approaches for the synthesis of recombinant proteins in E. coli and discuss recent progress in this ever-growing field.